Exposure to traumatic events and perceptual priming in forcedly displaced Colombian population in Ecuador - Reyes Valenzuela, Carlos; Martos-Méndez, María José; Blanco Abarca, Amalio; Blanco, Rubén (Anales de Psicología / Annals of Psychology, 2019)
In line with the hypothesis that PTSD is a memory disorder, recent studies on perceptual priming have focused on identifying the differences between population with and without Post-Traumatic Stress Disorder (PTSD). This study addresses priming in people who have been exposed to traumatic experiences of forced displacement. To that end, three categories of the word “trauma” (i.e., of threat, emotional and judicial) and a category of “neutral” words, which shared their three-letter root were chosen. The participants were 44 Colombian refugees and asylum seekers living in Ecuador with or without PTSD. The results of our study point that people with PTSD have higher perceptual priming in the threat and emotional categories, and asylum seekers show higher priming in the judicial category. The implications for studies that address the impact of political violence are discussed.